Authentic Existence: Bridging Phenomenology and Stoicism - Leitlande, Gita (Problemos, 2022)
The aim of this article is to provide comparative research of the concept of authentic existence in Stoicism and Phenomenology. The analysis in the article is carried out by comparing select authors’ understanding of a few key concepts which appear to be the most alike: authentic and inauthentic existence, personal renewal, seeking cosmologic framework for ethics, being part of community, and the role of death in shaping awareness of authentic existence. The analysis concludes that there are various degrees of convergence in all concepts considered in the article, which allows the argument that despite substantial differences between philosophies, concepts of authentic existence of Stoicism and Phenomenology at times have compatible aspects, and even complement each other.